ANALISIS USAHATANI DAN PEMASARAN BUAH NAGA (Hylocereus costaricensis) DI DESA SANGGULAN KECAMATAN SEBULU KABUPATEN KUTAI KARTANEGARA (Analysis of Farming and Marketing of Dragon Fruit (Hylocereus costaricensis) in Sanggulan Village Sebulu Subregency Kutai Kartanegara Regency) - NDAN IMANG; FIRDA JUITA; ALFRED HONESTMAN (Universitas Mulawarman (University of Mulawarman), 2019)
Dragon fruit is one of the commodities with the increasing prospective in the market. The increased of demand and consumption of dragon fruit needs ways to increase productivity in some centres of production. The purposes of this study were to analyze production, cost, revenue, income, R/C ratio, marketing channel, margin, and profit of marketing of dragon fruit. The study was conducted from September to December 2018 in Sanggulan Village, Sebulu Subregency, Kutai Kartanegara Regency. The sampling method used census and snowball. Data collected were the primary and secondary data. Data analysis was done to calculate cost, revenue, income, R/C ratio, and marketing margin. The average of production, cost, revenue, and income of dragon fruit was as many as 12,038.00 kg ha-1 year-1, IDR63,266,389.00 ha-1 year-1, IDR120,583,333.00 ha-1 year-1, and IDR57,316,944.00 ha-1 year-1, respectively. R/C ratio is 1.91 that meant dragon fruit farming is feasible to farm. Marketing channel is two levels from farmer to trader to retailer to consumer. Marketing margin owned by trader and retailer was IDR2,000.00 kg-1 and IDR3,000.00 kg-1, respectively. Marketing profit which received by trader and retailer was as much as IDR1,979.00 kg-1 and IDR2,985.00 kg-1, respectively.